Analysis of the efficiency of the attack from the second line, at the level of men senior, in the volleyball game - Cojocaru, A. M.; Cojocaru, M. (Journal of Physical Education and Sport, 2019)
The technical evolution of any athletic event is closely related to the evolution of the other components of The novelty regarding the concept of play in performance volleyball is determined by the psychic peculiarities of the player but also by his behavior in cooperation and teamwork, but also by the cohesion of the players. Once the ball has been thrown in, only the final attack matters In the game of volleyball, the main purpose is to win all the points put into play, which is achieved by building the attack, which must be effective. The purpose of the study is the analysis of the attack in the second line, in senior teams, participating in the National Championship, which can become an orientation in the preparation of the teams, so as to produce an increase in the efficiency of the attack in the second line, which would lead to win the matches. For this we used as research methods, bibliographic study, computer recording, statistical-mathematical method and that of graphical representations. Studying the choice of the most appropriate moment to use the attack from the second line during the game, is a modern trend that, by generalization, can contribute to improving the sporting performance of volleyball players. The use of the attack in the second line during the conduct of an official match, according to the few previous studies carried out by some researchers in the field of volleyball, reveals numerous opportunities to realize the point. Key words: efficiency, game, attackfrom second line, volleyball, seniors